Private Madrasah Development Strategy at Madrasah Aliyah - Muhammad Hanafi Rumatiga; Syahruddin Usman; Harbani Pasolong; Munawir Kamaluddin; Muhammad Yusuf (Tafkir: Interdisciplinary Journal of Islamic Education, 2023)
This study aims to analyze the Private Madrasah Development Strategy at Madrasah Aliyah Al-Hilal Dobo Aru Islands, Maluku. Qualitative research with the type of case study, data sources from madrasa heads, teaching staff, heads of administration, heads of madrasah committees, writings, books, and documents related to the object under study. Collecting data through observation, interviews, and documentation. Data analysis utilizing data reduction, data presentation, and conclusion. Testing the validity of the data is done by extending observations, increasing persistence, and triangulation. The results of the study show that Madrasah Aliyah Al-Hilal Dobo Aru Islands Maluku has the motto One Step Forward. The strategy undertaken is to carry out planning by involving internal and external stakeholders, implementing the strategy by forming a team that is divided into several fields that are specifically tasked with being responsible for the process of implementing the programs that have been determined, then evaluated in three stages, namely short term, medium term, long-term. Efforts made include improving teachers' teaching abilities, optimizing the use of media and educational facilities, carrying out routine supervision, establishing cooperation with the community, and applying strict discipline.